Efektivitas cognitive behavior therapy (CBT) terhadap tingkat stres orang tua dengan anak gangguan perkembangan saraf: A literature review - Cahyani, Cahyani; Regita, Ardhia Khanna; Nani, Nani; Desiyani, Desiyani (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Neurodevelopmental disorders (NDD) in children and adolescents, including attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), intellectual disabilities (ID), learning disabilities (LD) and others can occur in the final stages of serious developmental disorders or disorders, especially functional, structural, and cognitive. Children's conditions like this cause parents to experience stress in their lives, which can affect their emotional and physical conditions and even their social interactions. There are various treatment methods to reduce anxiety, stress, and depression, improve mental health, and improve problem-solving skills. One of these interventions is cognitive behavioral therapy (CBT). Purpose: To test the effectiveness of cognitive behavioral therapy (CBT) on stress levels in parents who have children with neurodevelopmental disorders. Method: Literature review research with article selection referring to the Preferred Reporting Items for Literature Review and Meta-Analysis (PRISMA). The databases used for article searches were Google Scholar, PubMed, and Science Direct. The keywords used were “cognitive behavioral therapy” AND “parenting stress” AND “neurodevelopmental disorder” AND “children”. The search was adjusted to the inclusion and exclusion criteria that had been prepared. The eligibility criteria for this systematic review were randomized controlled trials (RCTs), English language, and fully accessible. Results: Based on the results of the review of seven articles, CBT is an appropriate and effective intervention to be given to parents who experience parenting stress. CBT has benefits for improving well-being and mindful parenting patterns in children with neurodevelopmental disorders. Future mindfulness-based parenting interventions should emphasize formal, planned meditation to improve outcomes. Although shortening formal meditation may make it more likely for parents to complete it, it is not yet known what dose (eg, duration of each meditation, frequency per week) is the optimal amount. Conclusions: CBT is effective in reducing parenting stress levels and is able to improve well-being and parenting patterns in children with neurodevelopmental disorders. Keywords: Children with Neurodevelopmental Disorders; Cognitive Behavioral Therapy (CBT); Parents; Stress. Pendahuluan: Gangguan perkembangan saraf (neurodevelopmental disorder/NDD) pada anak dan remaja, termasuk attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), gangguan intelektual (ID), learning disabilities (LD) dan lainnya dapat terjadi pada tahap akhir yang serius atau ketidakteraturan perkembangan, terutama fungsional, struktural, dan kognitif. Kondisi anak seperti ini menyebabkan orang tua mengalami stres dalam kehidupannya, sehingga dapat memengaruhi kondisi emosional dan fisiknya bahkan interaksi sosialnya. Terdapat berbagai metode pengobatan untuk mengurangi kecemasan, stres, dan depresi, meningkatkan kesehatan mental, serta meningkatkan kemampuan memecahkan masalah. Salah satu intervensi tersebut adalah cognitive behavior therapy (CBT). Tujuan: Untuk mengkaji efektivitas cognitive behavior therapy (CBT) terhadap tingkat stres pada orang tua dengan anak gangguan perkembangan saraf. Metode: Penelitian literature review dengan pemilihan artikel mengacu pada Preferred Reporting Items for Literature Review and Meta-Analysis (PRISMA). Basis data yang digunakan untuk pencarian artikel adalah Google Scholar, PubMed, dan Science Direct. Kata kunci yang digunakan adalah “cognitive behavioral therapy” AND “parenting stress” AND “neurodevelopmental disorder” AND “children”. Pencarian disesuaikan dengan kriteria inklusi dan eksklusi yang telah disiapkan. Kriteria kelayakan tinjauan sistematis ini adalah uji coba terkontrol acak (RCT) , bahasa Inggris, dan dapat diakses secara keseluruhan. Hasil: Berdasarkan hasil telaah tujuh artikel, CBT merupakan intervensi yang sesuai dan efektif untuk diberikan kepada orang tua yang mengalami stres pengasuhan anak. CBT memiliki manfaat untuk meningkatkan kesejahteraan dan pola pengasuhan yang penuh perhatian pada anak-anak dengan gangguan perkembangan saraf. Intervensi pengasuhan anak berbasis perhatian penuh di masa mendatang harus menekankan meditasi terencana formal untuk meningkatkan hasil. Meskipun memperpendek meditasi formal dapat membuatnya lebih memungkinkan bagi orang tua untuk menyelesaikannya, belum diketahui berapa dosis (misalnya, durasi setiap meditasi, frekuensi per minggu) yang merupakan jumlah optimal. Simpulan: CBT efektif dalam menurunkan tingkat stres pengasuhan dan mampu meningkatkan kesejahteraan dan pola pengasuhan pada anak dengan gangguan perkembangan saraf. Kata Kunci: Anak Gangguan Perkembangan Saraf; Cognitive Behavior Therapy (CBT); Orang Tua; Stres.